Rock slope stability - Kliche, Charles A., 1951- (Society for Mining, Metallurgy, and Exploration, 1999)
Annotation. Whether you're involved in surface mine design, surface mine production, construction, education, or regulation, this is an important new book for your library. It describes the basic rock slope failure modes and methods of analysis--both kinematic and kinetic techniques. Chapters include geotechnical and geomechanical analysis techniques, hydrology, rock slope stabilization techniques, and geotechnical instrumentation and monitoring. Numerous examples, drawings, and photos enhance the text.
Keywords: Rock slopes.; Rock mechanics.; Stability.; elektronické knihy; electronic books